Performance improvement of solar distiller using hang wick, reflectors and phase change materials enriched with nano-additives. (March 2022) - AbuShanab, Waheed Sami; Elsheikh, Ammar H.; Ghandourah, Emad Ismat; Moustafa, Essam B.; Sharshir, Swellam W.
Abstract: The role of using nano-based thermal storage material filled into trapezoidal hang wick in a pyramid solar distiller is under study. The study underwent three stages of examination; after the material preparation. First, the pyramid distiller had a trapezoidal hang wick with pure phase change material (PCM) inside the cavity of the hang wick structure. Secondly, the pure PCM was replaced by PCM enriched with CuO-nanoparticles (NPS) based. Thirdly, four flat reflectors were established around the distiller in addition to the hang wick and the CuO-NPs based PCM. The water yield increase for the three investigated cases compared with the conventional single-slope solar distiller was 59.87%, 107.52%, and 154.38%, respectively, as the third case had daily productivity of 8.14 L/m 2 . Furthermore, the thermal and exergy efficiencies and the heat transfer coefficients have been carried out and showed that there is an increase in the thermal efficiency, energy efficiency and total heat transfer coefficient of the third case (the best case) by, 152.1%, 281%, and 68.59% compared with the conventional distiller. Moreover, cost and environmental analyses were carried out. The liter of freshwater costs 0.0089 $ with saving ratio of 41.06%. For the environmental requirements, the third case reduced the CO2 emission by 10.27 ton-CO2 /year, which corresponds to cost-saving by 148.96 $/year.